Development and characterization of a new set of 164 polymorphic EST‐SSR markers for diversity and breeding studies in rubber tree (Hevea brasiliensis Müll. Arg.). Issue 3 (11th February 2014) - Cubry, Philippe; Pujade‐Renaud, Valérie; Garcia, Dominique; Espeout, Sandra; Le Guen, Vincent; Granet, Françoise; Seguin, Marc; Ordon, F.
Abstract Despite its economic importance and recent genome release, the need for molecular tools for Hevea brasiliensis is high. In the frame of a disease resistance study, EST sequences were retrieved from public database or generated by sequencing SSH libraries. Sequences were trimmed and microsatellite motifs searched using an ad hoc bioinformatic pipeline, and pairs of primers for the amplification of candidate markers were generated. We found a total of 10 499 unigenes from both sources of sequences, and 673 microsatellites motifs were detected using the default parameters of the pipeline. Two hundred sixty‐four primer pairs were tested and 226 (85.6%) successfully amplified. Out of the amplified candidate markers, 164 exhibited polymorphism. Relationships based on dendrograms using simple matching index and diversity statistics based on EST‐SSRs were compared with Genomic SSRs, showing the potentialities of EST‐derived microsatellites for resistance studies but also for population genetics approaches.